أثر استخدام التسويق الرقمي في بنـاء الصورة الذهنيَّة للوجهة السيـاحية دراسـة استطـلاعية لـآراء عينة من مستـخدمي الـوسائط الرقميـة (El-Wahat Journal for Research and Studies, 2025)
Our Study Aims To Determine The Degree Of Using Digital Marketing Tools, Including Websites, Social Media Platforms, Email, And Mobile Phones, And Their Effect On Shaping The Mental Image Of The Tourist Destination.To Determine The Level Of Application Of These Digital Media, The Relationship Between Digital Marketing And The Image Of The Tourist Destination Was Analysed, Alongside Studying The Effect Of These Digital Techniques On Shaping The Preferences And Impressions Of The Audience During Destination Selection.We Have Generated, Distributed, And Analysed E-Questionnaire Using SPSS Of Sample From 143 Participants For The Goal Of Examining Study Hypotheses And Statement Of The Problem. The Results Have Shown A Moderate Correlation Between Digital Marketing And The Tourism’s Destinations Mental Image, Indicating A Positive Digital Marketing Effect Among The Sample Individuals During Their Destination Selection.Key Words: Digital Marketing; Digital Marketing Techniques; Mental Image Of Tourism Destination.